Motivation, Emotion, Learning Experience, and Second Language Comprehensibility Development in Classroom Settings: A Cross‐Sectional and Longitudinal Study. Issue 3 (26th June 2018) - Saito, Kazuya; Dewaele, Jean‐Marc; Abe, Mariko; In'nami, Yo
Abstract: This study presents a cross‐sectional and longitudinal analysis of how 108 high school students in English as a foreign language (EFL) classrooms enhanced the comprehensibility of their second language (L2) speech according to different motivation, emotion, and experience profiles. Students' learning patterns were primarily associated with their emotional states (anxiety vs. enjoyment) and secondarily with their motivational dispositions (clear vision of ideal future selves). Students' anxiety together with weaker Ideal L2 Self related negatively to their performance at the beginning of the project—performance that they had achieved after several years of EFL instruction. Students' enjoyment together with greater Ideal L2 Self predicted the extent to which they practiced and developed their L2 speech within the 3‐month framework of the project. Results suggest that more frequent L2 use with positive emotions directly impacts acquisition, which may in turn lead to the lessening of negative emotions and better long‐term L2 comprehensibility. Open Practices: This article has been awarded an Open Materials badge. Study materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .